Physiological State and Learning Ability of Students in Normal and Virtual Reality Conditions: Complexity-Based Analysis - Babini, Mohammad H; Kulish, Vladimir V; Namazi, Hamidreza (JMIR Publications, 2020)
BackgroundEducation and learning are the most important goals of all universities. For this purpose, lecturers use various tools to grab the attention of students and improve their learning ability. Virtual reality refers to the subjective sensory experience of being immersed in a computer-mediated world, and has recently been implemented in learning environments. ObjectiveThe aim of this study was to analyze the effect of a virtual reality condition on students' learning ability and physiological state. MethodsStudents were shown 6 sets of videos (3 videos in a two-dimensional condition and 3 videos in a three-dimensional condition), and their learning ability was analyzed based on a subsequent questionnaire. In addition, we analyzed the reaction of the brain and facial muscles of the students during both the two-dimensional and three-dimensional viewing conditions and used fractal theory to investigate their attention to the videos. ResultsThe learning ability of students was increased in the three-dimensional condition compared to that in the two-dimensional condition. In addition, analysis of physiological signals showed that students paid more attention to the three-dimensional videos. ConclusionsA virtual reality condition has a greater effect on enhancing the learning ability of students. The analytical approach of this study can be further extended to evaluate other physiological signals of subjects in a virtual reality condition.